4. CURRENT STATUS OF HEALTH COMMUNICATION ACTIVITIES IN HOSPITALS UNDER THE MINISTRY OF HEALTH IN 2024 (Tạp chí Y học Cộng đồng, 2025)
Objective: This study aims to assess the current state of health communication activities at hospitals under Vietnam’s Ministry of Health in 2024, focusing on human resources, infrastructure, funding, communication tools, and the utilization of media platforms.Methods: A cross-sectional descriptive study was conducted at 35 hospitals nationwide. Data were collected from 2024 institutional reports and semi-structured online surveys with health education communication (HEC) officers. A total population sampling method was applied. Quantitative data were analyzed using Epidata 3.1 and SPSS 20.0 for descriptive statistics, while qualitative responses were thematically analyzed using a deductive approach.Results: The findings revealed that the average number of personnel involved in communication activities per hospital was 9.14, with part-time staff (5.29) outnumbering full-time staff (3.86). Most personnel held university degrees and had more than five years of experience. The average communication budget per hospital was 190.57 million VND, mainly from hospital self-financing. All hospitals had dedicated communication rooms, with an average of 25 communication corners and essential communication tools. Facebook, websites, and fanpages were the most commonly used channels, with content updated on a weekly or more frequent basis. Despite efforts, many hospitals did not fully meet their communication activity targets in terms of volume and content quality.Conclusion: While health communication infrastructure and multi-channel outreach strategies are in place, challenges remain in workforce adequacy, funding disparities, and evaluation practices. To enhance the effectiveness and sustainability of hospital communication systems, increased investment in human resources, modern technologies, and structured performance evaluation mechanisms is urgently needed.
Keywords: Health communication; Hospital media strategy; Human resources; Digital platforms; Vietnam health system.